2018
DOI: 10.1590/abd1806-4841.20187452
|View full text |Cite
|
Sign up to set email alerts
|

Translation into Portuguese language (Brazil), transcultural adaptation and validation of the quality of life questionnaire in female pattern hair loss (WAA-QoL-BP)

Abstract: BackgroundFemale pattern hair loss (FPHL) is a common complaint in adult women and inflicts major impact in quality of life, however, there is no specific questionnaire available in Portuguese for such evaluation.ObjectivesTranslation into Brazilian Portuguese, cultural adaptation and validation of the WAA-QoL (Women's Androgenetic Alopecia Quality of Life Questionnaire).MethodsMethodological study. After authorization by the author, cultural (linguistic) translation and adaptation to Portuguese of the WAA-QoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…We performed a reanalysis of pooled data from crosssectional studies in Brazil that utilized the DLQI-BRA to assess the HRQOL impact of 14 dermatoses on 1286 patients [25][26][27][28][29][30][31][32][33]. Furthermore, sex, age, educational status and physical and psychological dimensions of the skin disorders were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a reanalysis of pooled data from crosssectional studies in Brazil that utilized the DLQI-BRA to assess the HRQOL impact of 14 dermatoses on 1286 patients [25][26][27][28][29][30][31][32][33]. Furthermore, sex, age, educational status and physical and psychological dimensions of the skin disorders were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was a result of pooled data from 14 crosssectional studies in Brazil that utilized the DLQI-BRA to assess HRQOL [25][26][27][28][29][30][31][32][33]. The sample size (n = 1286) was assumed to be sufficient in the IRT parameter estimation, dimensionality assessment and DIF and generalized linear model analyses, adjusted for up to eight dummy variables [50][51][52].…”
Section: Methodsmentioning
confidence: 99%
“…Blinded analysis of the trichoscopic images was performed by using TrichoLAB Hair-to-Hair Matching technology (Bad Birmbach, Germany). Secondary outcomes were change in terminal hair density, global photographic evaluation (by 3 board-certified dermatologists), quality-of-life evaluation with the Women's Androgenetic Alopecia Quality of Life Questionnaire, 3 and Sinclair hair shedding score (6-point scale). 4 Outcomes were compared according to time and group (over time) by linear mixed-effects models.…”
mentioning
confidence: 99%
“…Only a few other studies have used the Waa-QoL. One study carried out in Brazil and another carried out in Australia had median scores of 58 and 46.5 respectively amongst their cohorts [13,22]. Comparatively the cohort in this study reported far worse QoL in relation to their hair loss.…”
Section: Discussionmentioning
confidence: 62%
“…Questions which scored the highest amongst participants were regarding patients feeling fearful of their hair loss continuing, having difficulty styling their hair and feeling self-conscious about people looking at their hair. These questions, particularly the first two have also scored the highest in previous studies, indicating it is something commonly found in different cohorts [13,22]. As these factors are shown to severely impact women's QoL, they can be targeted by clinicians when managing patients.…”
Section: Discussionmentioning
confidence: 84%